2008
DOI: 10.1007/s12072-008-9060-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative redox status in alcoholic liver disease and nonalcoholic fatty liver disease

Abstract: Purpose Altered redox status has been implicated in pathogenesis of alcoholic liver disease (ALD) as well as in nonalcoholic fatty liver disease (NAFLD). This study was planned to find the relative role of redox status in these two diseases. Methods A total of 44 patients with ALD and 32 patients with NAFLD and 25 apparently healthy controls were included in the study. Redox status was estimated by measuring oxidative stress (superoxide dismutase (SOD) and lipid peroxidation products as thiobarbituric acid rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Thiobarbituric acid reactive substances (TBARS), which represent products of lipid peroxidation, were significantly increased among patients with NAFLD than in the other two groups [44]. In another study by the same group, patients with alcoholic liver disease were found to have greater degree of redox imbalance than patients with NAFLD [45].…”
Section: Oxidative Stressmentioning
confidence: 96%
See 1 more Smart Citation
“…Thiobarbituric acid reactive substances (TBARS), which represent products of lipid peroxidation, were significantly increased among patients with NAFLD than in the other two groups [44]. In another study by the same group, patients with alcoholic liver disease were found to have greater degree of redox imbalance than patients with NAFLD [45].…”
Section: Oxidative Stressmentioning
confidence: 96%
“…A high ratio of reduced glutathione (GSH) to oxidized glutathione (GSSG) protects against oxidative stress. In patients with NAFLD, hepatic GSH levels are reduced, but the redox imbalance may be lower than that seen in patients with alcoholic liver disease [44][45][46][47].…”
Section: Oxidative Stressmentioning
confidence: 96%
“…The ''first hit'' causes hepatic lipid accumulation and leaves stressed hepatocytes susceptible to injury. The ''second hit'' advances hepatic steatosis to NASH by induction of inflammation and oxidative stress, causing hepatocyte damage and death (10,56,59,66). NASH can occur with or without fibrosis and then progress to end-stage liver disease, cirrhosis, and hepatocellular carcinoma (13).…”
Section: Glrxmentioning
confidence: 99%
“…α-tocopherol supplementation to rats chronically exposed to ethanol has been shown to prevent the formation of Mallory bodies and inflammatory infiltration of the liver but not increased apoptosis, inspite of increased antioxidant gene expression [6]. Several groups have shown that subjects with alcoholic liver disease have been shown to have significantly lower plasma vitamin E levels [9,37,38] and a higher degree of redox imbalance [7]. However, the results of long-term vitamin E supplementation have been controversial and inconsistent [5,14,39,40] although positive results have been reported in patients with non-alcoholic fatty liver [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The consequential change in redox imbalance caused by ROS generation has been observed in patients with alcoholic liver disease [7] but attempts to ameliorate these disturbances through the administration of antioxidants has met with mixed results [1,8,9]. In contrast to this, many animal model studies (principally with rodents) have shown that these antioxidants and vitamin E in particular do have mitigating effects on free radical damage of the liver related to alcohol abuse [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%